(untitled) (Bangladesh Journal of Agricultural Research, 2023)
Vegetable production in the waterlogged condition is the main challenge in Southwest Bangladesh and to address the problem the present investigation was undertaken to determine the prospect and profitability of hanging sack vegetable cultivation in the waterlogged condition under various levels of organic matter. The investigation comprised three of vegetables such as Brinjal, Tomato, and Okra in hanging sacs under three soil and organic matter combinations at Germplasm Center of Agrotechnology Discipline, Khulna University Bangladesh from November 2018 to March 2019. Three soil+cowdung combinations were T0= 100% soil, T1= 50% soil+50% cowdung, T2= 75% soil+ 25% cowdung, T3=25% soil+ 75% cowdung replicated seven times to produce the less erroneous results. Brinjal in the hanging sac had significantly better biological yield (28.92 t/ha), net return (451,000Tk./ha)and benefit-cost ratio (BCR) (2.08)over okra or tomato when the sac was filled with 75% cowdung + 25% soil. The higher price plus advanced yield contributed to enhancing the profitability of brinjal. These results will inform decision-making about cropping system modification that can be adopted by vegetable growers of Southwest Bangladesh to considerably reduce fallow waterlogged areas and enhanced vegetable production in waterlogged conditions. Bangladesh J. Agril. Res. 46(1): 35-42, March 2021